2022
DOI: 10.1002/srin.202100627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbide Precipitation on “Precipitation Plasticity” and Residual Stress during Tempering

Abstract: Tempering is an important method for controlling the residual stress of metallic materials. Experience has indicated that increasing the tempering temperature and extending the tempering time reduces the residual stress. However, the micromechanism of residual stress evolution during tempering is not well understood.Ritter et al. [1] believed that the changes in the mechanical behavior of a material during tempering are the main reason for the relaxation of residual stress and attempted to reveal the internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…) Simultaneous Equation. ( 6), the strain disturbance can be obtained from 𝜺 𝑖𝑗 ′ = 𝑻 𝑖𝑗𝑘𝑙 : 𝝈 ̅ 𝑘𝑙 (13) where…”
Section: Simulation Of Elastic Responsementioning
confidence: 99%
“…) Simultaneous Equation. ( 6), the strain disturbance can be obtained from 𝜺 𝑖𝑗 ′ = 𝑻 𝑖𝑗𝑘𝑙 : 𝝈 ̅ 𝑘𝑙 (13) where…”
Section: Simulation Of Elastic Responsementioning
confidence: 99%
“…Subsequently, Kaiser et al [9][10][11] found that plastic behaviour similar to phase transformation plasticity occurs in cementite precipitation stage during the tempering process and predicted the evolution of residual stress during tempering by the Greenwood-Johnson model. Ding et al 12,13 confirmed the existence of irreversible plastic behaviour during carbide precipitation. They further pointed out that this plastic behaviour caused by carbide precipitation is the main reason for the relaxation of residual stress during tempering.…”
Section: Introductionmentioning
confidence: 96%